Rest interval between jumps during track and field jumping competitions - Veligekas, P.; Bogdanis, G. C.; Stabolitis, C.; Frantzis, D. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Field jumping events may be categorized as horizontal jumps (long and triple jump) and vertical jumps (high jump and pole vault). In the horizontal jumps each athlete performs three jumps and the eight athletes with the best valid performances are allowed three additional trials. Vertical jumps are "open ended", and an athlete may commence at any height and may continue to any subsequent height, until failure (IAAF, 2012). Analysis results from Olympic Games and World Championships (IAAF competition archive, www.iaaf.org) showed that high jumpers and pole vaulters performed on average 9±2 jumps and 8±1 vaults. However, it is now known if the recovery time between the jumps is always adequate. The aim of this study was to record the time interval between trials during official competitions in the four field jumping events (long, triple, high jump and pole vault). Methods: Data acquisition was performed during three different indoor competitions (one of them was the National Championships). The total number of athletes in all three competitions was 63 males and 61 females for the horizontal jumps and 54 males and 52 females for the vertical jumps. The time elapsed from the end of each trial until the start of the next was recorded for every athlete by two observers. Results: In the long and triple jump, the rest interval between the first three jumps was 10.0±0.2 min, while it increased to 12.5±0.5 min between jumps 3 and 4. This was due to the change in the order that the athletes jumped after the third trial, where only 8 athletes continued to compete. The rest intervals before the last two jumps were decreased to 6.85±0.2 min. In the high jump and pole vault, the rest interval between the first two jumps was on average 6.8±0.5 min and declined steadily until the sixth jump to about 4.0±0.4 min. Thereafter, the rest interval declined by a small amount, depending on the number of participants left. Discussion: The main findings of this study were that there is significantly less time between trials in the horizontal compared with the vertical jumps. Thus, athletes who compete in the vertical jumps have about 40% less time for recovery between their jumps while every subsequent trial must be done at a higher height. The relatively short recovery time in the vertical jumps indicates that some athletes may not be metabolically ready to perform maximally during the later stages of the competition (Dawson et al., 1997). These finding may have implications for the design of specific training programs that simulate competition, especially in the vertical jumps and also for competition tactics.